INTEGRATING ARTIFICIAL INTELLIGENCE INTO LOCAL DEVELOPMENT: THE POTENTIAL OF AI TO IMPROVE THE MANAGEMENT AND EFFECTIVENESS OF LOCAL ACTION GROUPS (LAGS) - Kaloyan Stoychev (Journal of Bio-Based Marketing)
This publication explores the potential of artificial intelligence (AI) to transform the activities of Local Action Groups (LAGs). Through qualitative and conceptual analysis based on contemporary scientific literature and good practices from Europe and around the world, a framework for possible applications of AI in five key areas is developed: automation of administrative processes, intelligent analysis of community needs, digital consulting support, predictive analysis and modeling, and identification of new partnerships. The study offers an interpretative reading of the opportunities, but also of the barriers to AI implementation, including technological, institutional, social, and ethical aspects. Recommendations for future action are formulated, including pilot implementation, capacity building, and strategic coordination at the national and local levels. The results highlight the need for an integrated and carefully structured approach to the digital transformation of local development, in which AI serves as a support to human participation rather than a substitute for it.